‘Avoidance Preening’, Displacement Behavior and Co-Dependency in Professional Team Sport: When Wants Become More Important Than Needs - Blake D. McLean; Donnie S. Strack; David T. Martin (International Journal of Sports Physical Therapy)
An athlete’s body plays an important role in their performance and well-being. However, game-relevant skills are better determinants of success, compared with physical fitness, in technically-driven team sports. In the professional era, over utilization of resources, in pursuit of physical optimization, can detract from time spent on priorities. Athletes’ non-strategic, time-demanding focus on physical preparation/treatments resembles avian ‘avoidance preening’, whereby stressful situations trigger birds to excessively preen in place of more productive activities. The purpose of this commentary is to explore the behaviors of resource-rich professional teams and the roles of staff dedicated to optimizing physical performance, including circumstances that foster avoidance behavior and create the potential for practitioners to encourage co-dependent relationships with athletes. To cultivate healthy/productive environments, the following is recommended: I) recognition of non-productive avoidance behaviors; II) eschewing unjustified, fear promoting, pathoanatomical language; III) fostering collaborative approaches; IV) encouraging utilization of psychology services; V) recognizing that optimal physical function and feeling good is rarely the primary goal in professional team sports.